Student Stress Management and Wellness Programs among Colleges of Pharmacy - Sally Arif; Kelly Moran; Ana Quinones-Boex; Shareen El-Ibiary (University of Minnesota Libraries Publishing, 2021)
Objective: To describe the programmatic stress-related interventions that colleges of pharmacy are providing for their students. Methods: A paper-based questionnaire was distributed to 80 college teams who attended two consecutive offerings of the American Association of Colleges of Pharmacy institute focused on promoting student well-being. The five-part questionnaire consisted of: 1) tracking and assessment of perceived student stress levels, 2) the types and formats of stress-coping interventions that are offered, 3) the measured impacts of any stress-coping interventions, 4) the level of faculty/staff training and involvement in student stress remediation, and 5) institutional demographics. Results: Of the 40 college teams responding to the survey there were similar numbers of private (44%) and public (56%) institutions. More than half (57.5%) reported measuring student stress levels. The most common interventions offered were counseling (95%), academic advising (82%), physical exercise support (77%), and relationship building activities (70%). Topics offered in the curriculum were most often related to handling substance abuse (50%), time-management (45%), and finances (40%).  A majority (79.5%) of schools reported they do not offer formal training on student stress and mental health to faculty and staff and do not formally assess the impact of stress and coping interventions.                                                                   Conclusion: Colleges of pharmacy are addressing student stress and well-being, yet variability exists in terms of assessment, interventions, and didactic offerings. Multiple barriers to improvement remain and mediating barriers and determining assessments for coping and interventions may be next steps for Colleges of Pharmacy.